Microstructural and wear investigation of FeCrC and FeCrC-NbB hardfacing alloys deposited with FCAW-S - Cunha, Mateus Codognotto (2025)
Wear is one of the main problems encountered in industrial operations, generating high costs due to equipment failures for constant replacement of parts. By implementing technologies designed to enhance wear resistance, losses can be minimized in industries such as mining, cement, sugar and ethanol, and steel production. A key solution to reducing maintenance costs from wear is the application of highly abrasion-resistant alloys through welded hardfacing on coated sheets. Therefore, the objective was to investigate the microstructure and wear resistance of two high chromium hardfacing alloys with Fe–C-Cr and Fe–C-Cr-Nb-B systems used in the manufacture of wear resistance, deposited using tubular wires. This study also aims to assess the variation in wear rate based on the alloy composition in the coatings. Firstly, the characterization of the materials was carried out through chemical and microstructural analysis through scanning electron microscopy (SEM), X-ray diffraction (XRD), and hardness. A comparative analysis of the friction coefficient and wear resistance was carried out using the ASTM G133–Linearly Reciprocating Ball-on-Flat Sliding Wear test, where the worn volume was analyzed by optical profilometry. The Fe–C-Cr-Nb-B system alloy presented higher hardness values and lower volume loss than the Fe–C-Cr system alloy due to the presence of niobium primary carbides dispersed throughout the coating, promoting greater matrix protection and, consequently, less abrasive wear. The results were coherent and provided data that can lead to a better selection of materials among solutions in the manufacture of wear-resistant sheets and hard coatings deposited by welding in the industry.